2016
DOI: 10.1371/journal.pone.0150405
|View full text |Cite
|
Sign up to set email alerts
|

Increased Case Notification through Active Case Finding of Tuberculosis among Household and Neighbourhood Contacts in Cambodia

Abstract: BackgroundGlobally, there has been growing evidence that suggests the effectiveness of active case finding (ACF) for tuberculosis (TB) in high-risk populations. However, the evidence is still insufficient as to whether ACF increases case notification beyond what is reported in the routine passive case finding (PCF). In Cambodia, National TB Control Programme has conducted nationwide ACF with Xpert MTB/RIF that retrospectively targeted household and neighbourhood contacts alongside routine PCF. This study aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 23 publications
2
67
0
2
Order By: Relevance
“…According to the study the pre and post intervention results were statistically significant which implies that educating of health workers on contact tracing will improve skills and case notification. Similarly a retrospective quasi-experimental cluster randomized design study among household and neighborhood contacts was conducted by [70] to ascertain the effectiveness of contact tracing to TB case-finding. The study is a qualitative study with intervention and control group using Xpert/MTB-RIF assay.…”
Section: Knowledge Of Contact Tracingmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the study the pre and post intervention results were statistically significant which implies that educating of health workers on contact tracing will improve skills and case notification. Similarly a retrospective quasi-experimental cluster randomized design study among household and neighborhood contacts was conducted by [70] to ascertain the effectiveness of contact tracing to TB case-finding. The study is a qualitative study with intervention and control group using Xpert/MTB-RIF assay.…”
Section: Knowledge Of Contact Tracingmentioning
confidence: 99%
“…The findings revealed a significant increase in number of cases detected in the intervention areas when compared to control areas, this underpins the significant of contact tracing process in TB case detection. [70] conducted a study on the impact of contact tracing of TB case detection and opined that contact tracing is a DOI: 10.4236/aid.2018.84016 comprehensive and strategic method of finding missing cases of TB.…”
Section: Knowledge Of Contact Tracingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in high burden areas have shown that active case finding among household contacts yields substantially more TB cases than passive case detection. (2,4,5) Kenya is among the 30 high TB burden countries in the world and is among the top 5 from sub Saharan Africa. Tuberculosis is the fourth biggest killer in Kenya after HIV/AIDS, maternal deaths and lower respiratory infections (1).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, there are few details about when and where participants are lost-to-follow-up, essential information for designing interventions to improve delivery of contact investigation. [3][4][5] Cascade analysis, frequently applied to understand cumulative losses along the HIV care continuum [6,7], can clarify the most important gaps in delivery of TB evaluation and care, and in so doing inform the design and targeting of interventions. [8] Identifying TB patients via household contact investigation depends on effectively completing four key steps in the delivery cascade: 1) scheduling visits to homes of index TB patients; 2) initiating these visits by physically reaching the homes of index patients; 3) screening all household contacts; and 4) ensuring that all symptomatic and high-risk contacts complete TB evaluation.…”
Section: Introductionmentioning
confidence: 99%